How teams overcome free-riding in strategic experimentation - Katharina Brütt (Tinbergen Institute, 2025)
Experimentation is at the core of innovation. This project studies collaborative experimentation in teams, focusing on the inherent two-dimensional free-riding problem induced by payoff and informational externalities. The discouraging force of observing others' unsuccessful experimentation and the attempt to keep one's team members optimistic theoretically result in inefficiently low experimentation in teams. In a laboratory experiment, I study how distinct elements of the experimentation environment affect this strategic experimentation. I vary (i) the observability of experimentation and (ii) whether agents work on joint or separate projects. Teams largely overcome the free-riding problem. Contrary to theoretical predictions, both the observability of experimentation and experimenting jointly increase experimentation levels. There is no lack of sophistication in updating beliefs that drives this, neither do subjects disregard their experimentation's effect on others. Instead, the data can be best explained by joint, observable experimentation creating incentives to 'lead by example' and setting norms of high experimentation.
Keywords: D81; D83; D91; 330; Strategic experimentation; Free-riding; Informational externality; Experiment